Dietary Codonopsis pilosula polysaccharides promote gut health and enhance immunity in Hu sheep - Zhao, Qing; Li, Wanning; Liu, Zilong; Li, Qiao; Ma, Youji (Frontiers in Microbiomes, 2025)
In recent years, there has been a growing emphasis on the use of plant polysaccharides in animal husbandry, attracting attention for their distinctive benefits and roles. These natural and eco-friendly feed additives not only enhanced livestock performance but also promoted intestinal health and strengthen immunity. This study utilized 16S rRNA high-throughput sequencing to investigate the effects of dietary Codonopsis pilosula polysaccharides on the gut microbiota of Hu sheep. Eighteen 3-month-old Hu sheep with similar body weight (19.60 ± 1.63 kg) and good body condition, were randomly allocated into three groups: a control group (CK) receiving a standard diet, and two trial groups: T1 (supplemented with 0.15% Codonopsis pilosula polysaccharides) and T2 (supplemented with 0.3% Codonopsis pilosula polysaccharides), with six animals in each group. The pre-trial period lasted for 7 days, followed by an experimental period of 90 days. Results demonstrated that incorporating Codonopsis pilosula polysaccharides into the diet markedly increased the acetic acid levels in the ileum. This incorporation was found to enhance the diversity of intestinal flora and influence the species composition and richness of the intestinal microbiota. LEfSe analysis revealed that the genus enriched in the three intestinal segments were primarily Candidatus_Saccharimonas, Christensenellaceae_R_7_group, Romboutsia, and UCG_005. The relative expression levels of Claudin, Occludin, and ZO-1 mRNA in the T1 group were found to be elevated compared to the CK and T2 groups across all three intestinal segments. In conclusion, these findings indicate that dietary supplementation with Codonopsis pilosula polysaccharides not only regulate the intestinal microbial composition of Hu sheep but also enhance their immune capacity by increasing the presence of specific beneficial bacteria, thus fostering the intestinal health of Hu sheep.